2001
DOI: 10.1093/oxfordjournals.rpd.a006423
|View full text |Cite
|
Sign up to set email alerts
|

210Pb, 210Po, 226Ra, U and Th in Arable Crops and Ovine Liver: Variations in Concentrations in the United Kingdom and Resultant Doses

Abstract: Concentrations of a range of naturally occurring radionuclides have been determined in the same crops grown at two sites in the UK. Ovine liver has also been studied. One site was in an area where concentrations in soil are typical of the UK (the 'control' site) and the other in an area where levels were well above average (the 'test' site). For an average adult consumer of all of the foodstuffs studied, the doses from consumption for the test site were about 4 times higher than those for the control site. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…For Cereals, Root crops, and Tubers, TFs were comparable. This is confirmed by observations by Ham et al (2001). Furthermore, these authors suggested that translocation from shoots to roots was negligible.…”
Section: Poloniumsupporting
confidence: 81%
See 1 more Smart Citation
“…For Cereals, Root crops, and Tubers, TFs were comparable. This is confirmed by observations by Ham et al (2001). Furthermore, these authors suggested that translocation from shoots to roots was negligible.…”
Section: Poloniumsupporting
confidence: 81%
“…in the vicinity of metal smelters (Pettersson et al, 1988;Ham et al, 2001;PietrzakFlis and Skowrofiska, 1995). The relative importance of these two pathways depends upon the concentration of the radionuclides in the soil, the soil-plant TF, and the rate of deposition onto the aboveground plant parts.…”
Section: Leadmentioning
confidence: 99%
“…In general, the observed concentrations of the nuclides were in the range of worldwide values [1][2][3][4][5][6][7], although higher than reference concentrations of natural radionuclides in foods assumed by UNSCEAR [13] which range from less than 0.001 to about 0.2 Bq/kg (see Table 1). Individual samples with high activity concentration (oats and rye) should be considered as special cases and the reason for the high values further investigated.…”
Section: Activity Concentrations In Food Samplesmentioning
confidence: 61%
“…Compared to the annual effective dose of no more than 200 Sv/a from natural radionuclides in food as assessed by UNSCEAR [13] this does not imply an unacceptable level of exposure. For comparative purposes the average annual effective dose from ingestion of natural radionuclides in Sv/a is estimated as 14.5 in Brazil [6], 23.9 in Nigeria [2], 83.9 in the UK [5], 110 in Korea [3] and 69-280 in Hong Kong [7].…”
Section: S218mentioning
confidence: 99%
See 1 more Smart Citation